2007
DOI: 10.1016/j.jhazmat.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Combined post-ozonation and biological treatment of recalcitrant wastewater from a resin-producing factory

Abstract: In this study, effluent from the biological treatment of wastewater from a resin-producing factory containing recalcitrant compounds was ozonated under different conditions. Afterwards, the biodegradability of the ozonated effluent was studied under anoxic conditions. The post-ozonation of the industrial effluent was performed using a wide range of ozone doses, from 1.8 to 29.5 mg L(-1)min(-1). After the biological treatment of the ozonated effluent, organic carbon and nitrogen removals from 27 to 97% and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 13 publications
0
10
0
2
Order By: Relevance
“…The oxidative chemical treatments have been used with the primary goal of oxidizing compounds that cannot be degraded by microorganisms (color provided by pigments such as melanoidins that are recalcitrant and toxic to microorganisms involved in biological wastewater treatment, and polyphenols (Kanimozhi and Vasudevan, 2010;Benitez et al, 2000)). It has been observed that chemical oxidation with ozone has properties desirable for pre-and post-treatment of industrial wastewater containing recalcitrant compounds (Aparicio et al, 2007;Chu et al, 2007;Gunten, 2003;Lage Filho, 2010;Rehman et al, 2006;Tuin and Bos, 2004). It has been shown recently that the combined use of ozonation and aerobic biodegradation, for the treatment of wastewater from the distillation of grape, is a good alternative technology for the reduction of recalcitrant compounds and organic matter expressed as COD (Beltra´n et al, 1999;Benitez et al, 2003;Sangave et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative chemical treatments have been used with the primary goal of oxidizing compounds that cannot be degraded by microorganisms (color provided by pigments such as melanoidins that are recalcitrant and toxic to microorganisms involved in biological wastewater treatment, and polyphenols (Kanimozhi and Vasudevan, 2010;Benitez et al, 2000)). It has been observed that chemical oxidation with ozone has properties desirable for pre-and post-treatment of industrial wastewater containing recalcitrant compounds (Aparicio et al, 2007;Chu et al, 2007;Gunten, 2003;Lage Filho, 2010;Rehman et al, 2006;Tuin and Bos, 2004). It has been shown recently that the combined use of ozonation and aerobic biodegradation, for the treatment of wastewater from the distillation of grape, is a good alternative technology for the reduction of recalcitrant compounds and organic matter expressed as COD (Beltra´n et al, 1999;Benitez et al, 2003;Sangave et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Post-treatment in an SBR (Sequencing Batch Reactor) system with a total cycle time of 24 h resulted in complete FA removal and a 98% reduction of COD; the COD concentration in the effluent was below 60 mg/dm 3 . Aparicio et al (Aparicio et al, 2007) analyzed the ozonation process of wastewater from a resin-producing factory and, afterwards, the biodegradability of the ozonated effluent was studied under anoxic conditions. It was proved that a combined post-ozonation and biological treatment can be applied to recalcitrant wastewater from a resin-producing factory.…”
Section: Treatment Of Wastewater From the Production Of Formaldehyde-mentioning
confidence: 99%
“…Benitez et al [20] demonstrated the COD removal for wine vinasses containing organic matter and aromatic compounds was enhanced (from 27.7% to 39.3%), when the combined ozonation and biological process was used. Aparicio et al [21] reported the use of combined wastewater treatment set up in a resin-producing factory. After biological treatment of the ozonated effluent, the organic carbon and nitrogen removal was increased from 27 to 97% and from 27 to 80%, respectively.…”
Section: Ozonation Followed By Biodegradationmentioning
confidence: 99%